2010
DOI: 10.17705/1cais.02602
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Based Differences in Consumer E-Commerce Adoption

Abstract: Among the many characteristics that impact the use of e-commerce, one that has received relatively little attention is gender. Extant evidence suggests that men and women differ in their beliefs regarding the use of information technology-related innovations, including e-commerce. However, less is known about how gender moderates the impact of various beliefs on behavioral intentions. In this study, we use a model derived from diffusion of innovations theory to examine gender differences in the degree to which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 63 publications
(92 reference statements)
5
51
2
Order By: Relevance
“…First, the study makes a theoretical contribution by showing that gender-specific differences exist in on-line shopping. This confirms previous research on the importance on gender in e-commerce [12,25,26,29,30] and extends our understanding of such difference by providing specific insights in these differences. In particular, this study has shown that males rank Accurate description of products (IQ1), Fair and transparent pricing (CQ1), Easy tracking and tracing of shipments (CQ4), and a Wide variety of products (CQ6) significantly more important than females.…”
Section: Implications For Researchsupporting
confidence: 88%
See 1 more Smart Citation
“…First, the study makes a theoretical contribution by showing that gender-specific differences exist in on-line shopping. This confirms previous research on the importance on gender in e-commerce [12,25,26,29,30] and extends our understanding of such difference by providing specific insights in these differences. In particular, this study has shown that males rank Accurate description of products (IQ1), Fair and transparent pricing (CQ1), Easy tracking and tracing of shipments (CQ4), and a Wide variety of products (CQ6) significantly more important than females.…”
Section: Implications For Researchsupporting
confidence: 88%
“…Although previous research has shown that gender matters, surprisingly little research has explicitly addressed gender differences in on-line shopping preferences [12,29,30]. Therefore, we intend to contribute to the e-commerce literature through reporting on what male and female on-line shoppers consider important features to create a positive shopping experience.…”
Section: Introductionmentioning
confidence: 99%
“…This attribute, therefore, is often seen extending a positive significant influence on adoption intentions. For instance, e-commerce adoption studies by Slyke, Belanger, and Hightower (2005) and Slyke, Lou, Belanger, and Sridhar (2010), and a mobile Internet adoption study by Hsu et al (2007) have supported its significant behavior. Thus, the posited hypothesis is as follows:…”
Section: Results Demonstrabilitymentioning
confidence: 99%
“…Studies citing visibility as an innovation attribute often tend to acknowledge Moore and Benbasat (1991) for recognizing this attribute in its exclusivity (Hsu et al, 2007;Slyke et al, 2005). By definition, this attribute is the measure of the degree to which the use of an innovation becomes apparent.…”
Section: Visibilitymentioning
confidence: 99%
“…Despite its lack of significance in Carter and Bélanger's (2005) research, image merits further investigation given the importance of a person's social image in influencing use of a government electronic service (Lean, Zailani, Ramayah, & Fernando, 2009) and consumer adoption of electronic-Commerce websites (Slyke, Bélanger, Johnson, & Hightower, 2010). Therefore, it is predicted that:…”
Section: Trust Of Internetmentioning
confidence: 99%